Corrective regulation with imperfect instruments - Eduardo Dávila; Ansgar Walther (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2022)
This paper studies optimal second-best corrective regulation, when some agents/activities cannot be perfectly regulated. We show that policy elasticities and Pigouvian wedges are sufficient statistics to characterize the marginal welfare impact of regulatory policies in a large class of environments. We show that a subset of policy elasticities, leakage elasticities, determine optimal second-best policy, and characterize the marginal value of relaxing regulatory constraints. We apply our results to scenarios with unregulated agents/activities, uniform regulation across agents/activities, and costly regulation. We illustrate our results in applications to financial regulation with environmental externalities, shadow banking, behavioral distortions, asset substitution, and fire sales.
Keywords: H23; Q58; G28; D62; 330; corrective regulation; second-best policy; Pigouvian taxation; policy elasticities; leakage elasticities; regulatory arbitrage; financial regulation; environmental externalities